Young disabled and LGBT+: negotiating identity. Issue 2 (3rd April 2019) - Toft, Alex; Franklin, Anita; Langley, Emma
Abstract: Disabled people are historically de-sexualized and labelled as non-sexual, incapable or uninterested in sex/relationships. This perception does much to reinforce social inequalities and misconceptions about disabled sexuality and gender. For young people who are LGBT + the task of negotiating their identity and making sense of who they are is challenging. Not only is their sexuality and gender invalidated by wider society, they are also marginalized and largely unsupported during a period of intense identity negotiation. Presenting findings from a UK-based qualitative project, this article explores how in the light of such challenges, young disabled LGBT + people understand, negotiate and enact their identities.